Biochemical characteristics of myofibrillar proteins of the fish parasite Isoparorchis hypselobagri (Trematoda) as survival traits in an oxygen-rich environment - Abbasi, Usma; Ahmad, Riaz; Hasnain, Absar-ul (Biological Letters, 2013)
We have investigated biochemical properties of myofibrillar proteins of the digenetic trematode Isoparorchis hypselobagri, which correlate with its survival in the oxygen-rich swim bladder of its host catfish (Wallago attu). The polypeptide composition of the trematode’s natural actomyosin (NAM) was striated-muscle-like, with the exception that a 98-kD polypeptide corresponding to paramyosin also existed in its sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) profiles. The profiles of immunoprecipitated NAM of the trematode support these inferences. Ca2+-sensitivity of myofibrillar contractility and Mg2+-ATPase activity of I. hypselobagri resembled troponin-linked calcium regulation of the host striated muscle. Myofibrillar permeability to water influx was insensitive to calcium chelation at neutral pH. However, the host swim bladder myofibrils displayed smooth-muscle-like polypeptide composition, pH dependence of contractility, Ca2+-sensitivity, ATPase activities, and inactivation kinetics. We propose 2 survival strategies that I. hypselobagri appears to have co-evolved: (i) fast-muscle-like musculature with exceptionally high contractility or ATPase activity; and (ii) type-II myosin resembling the host muscle in functional plasticity.